Polish Impact Barometer as a Tool to Measure Business Contribution to The Achievement of The Sustainability Development Goals - Joanna KRASODOMSKA (Communications of International Proceedings, 2020)
The important role of business in the realization of the Agenda 2030 commitments is widely accepted. Sustainable Development Goals (SDGs), which are at the heart of the Agenda, are nowadays among the key topics in corporate practices and reporting. The paper aims to investigate the situation in Poland as regards the SDGs achievement with a particular focus on companies indicated as the first members of the Impact Barometer Programme. The research uses available official NGO’s reports, information gathered via SDGs-related website and selected companies’ communications. The study findings show that the engagement of the companies operating in Poland in practices and disclosures linked to the SDGs accomplishment has been increasing. However, according to the information currently available, the Impact Barometer is used by eight companies, and the identified examples show that corporate disclosure is fragmented and, in some areas, impossible to compare. The paper acknowledges the need for future research in the field of the corporate practice and reporting related to the SDGs and draws attention to the negative SDGs-washing phenomena. The results of this study might be useful for researchers, practitioners, and other stakeholders focused on striving for a more sustainable future.
Keywords: SDGs; non-financial reporting; sustainable development; Poland.